Climate information training of trainers manual and guide: For extension officers on interpretation and use of agrometeorological information and products for climate-resilient agriculture and food security - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Guide aims to provide extension officers, farmers and intermediaries with appropriate knowledge on utilization of climate services provided by TMA, that is tailored for agrometeorological applications (and services) in Tanzania.